2022
DOI: 10.24042/ajpm.v13i1.11680
|View full text |Cite
|
Sign up to set email alerts
|

Digital comic learning media based on character values on students’ critical thinking in solving mathematical problems in terms of learning styles

Abstract: To prepare students to compete in 21st-century skills, the Ministry of Education and Culture of the Republic of Indonesia integrates character education into school subjects. However, as a medium, comics do not contain the level of character values, exploration, and critical thinking skills in problem-solving on geometry material. Therefore, the aim of this study is to produce digital media based on character values on mathematical critical thinking skills in solving problems related to learning styles for eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 36 publications
3
31
0
10
Order By: Relevance
“…The results of the study indicated that educators working in inclusive schools fell somewhere in the middle of the three categories. On the other hand, the presentation material that is used in presentations is based on modified versions of media that was made by other individuals (Darmayanti et al, 2022). This content was not developed by the persons giving the presentations.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study indicated that educators working in inclusive schools fell somewhere in the middle of the three categories. On the other hand, the presentation material that is used in presentations is based on modified versions of media that was made by other individuals (Darmayanti et al, 2022). This content was not developed by the persons giving the presentations.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study indicated that educators working in inclusive schools fell somewhere in the middle of the three categories. On the other hand, the presentation material that is used in presentations is based on modified versions of media that were made by other individuals (Darmayanti et al, 2022). This content was not developed by the persons giving the presentations.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Darmayanti, Sugianto, Baiduri, Choirudin, and Wawan (2022), the aim was to produce digital environments based on character values based on mathematical critical thinking skills in solving the problems related to the learning styles of eighth-grade students and as a result, the digital comics learning environment was determined by the verification of the values of the material expert. It is also seen that, based on the confirmation of the media expert, it is seen that eighthgrade students benefit from their mathematical thinking skills.…”
Section: Discussionmentioning
confidence: 99%